Testing The Antibacterial Effectiveness of Black Cumin Extract on The Growth of Bacteria Bacillus Cereus Disk Diffusion Method - Yuliati, Yuliati (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2024)
The main components of volatile oils are thymoquinone, thymohydroquinone, thymoquinone, thymol, and tannin which have been proven to be able to inhibit bacterial growth. This research was conducted to determine the antibacterial effectiveness of black cumin against the growth of Bacillus cereus bacteria with various concentrations of 10%, 25%, 50%, 75%, and 100% using the diffusion method. The type of research used by researchers is experimental. In this study, the disk disc method was used with concentrations of 10% 25%, 50%, 75%, and 100% using Amoxicillin 0.3% as a positive control for Bacillus cereus bacteria with repetition three times, by soaking the disc for 15 minutes in each concentration and attach the disc to media that has been inoculated with Bacillus cereus bacteria. Based on research results from the results of measurements of the inhibitory zone of the Bacillus cereus bacterium, it is included in the weak category with all concentrations showing an inhibitory zone with an average diameter of 8.67 mm, 10.67 mm, 12 mm, 16.33 mm, and 17.67 mmm. The conclusion from research on the antibacterial effectiveness of black cumin extract can inhibit the growth of Bacillus cereus bacteria in the weak inhibition category.